Eschatology of the old believers: social discourse - Grigorenko Andrey Yur’evich (Религия, церковь, общество, 2014)
Eschatology is an imminent phenomenon of waiting the end of the world of the Christian Church throughout its history. It has many dimensions, one of which is a practical refraction expressed in ideas of social chiliasm. Interconnection of the idea of the Second Coming with the socio-economic upheavals has been always emphasized by scholars, and this article gives a brief retrospective analysis of these relationships. The author states that starvation of folks was one of the causes of the chiliastic ideas and led to social protest in different eras of European history, starting from ancient civilizations till Thomas Münzer revolt during German Reformation. The researcher demonstrates an accurate use of Marxism methodology, that still can provide a fresh glance on some subjects. The author focuses on the Russian Old Believers’ tradition and shows both its universal character and national specifics. The study basing on careful analysis of source data gives amount of key points, when religious reflection of the schematics led not to escape and rejection of the “world”, but to protest and struggle with the official Church, that was seen in traditions of Eastern philosophy as integral part of the State. The author comes to conclusion that the impact of social and political upheaval on the structure of the Old Believers’ discourse was stronger than it seems at first glance.